Influence of interspecific competition on mule deer birthing and rearing site selection. Issue 1 (21st September 2022) - Sallee, Daniel W.; McMillan, Brock R.; Hersey, Kent R.; Petersen, Steven L.; Larsen, Randy T.
Abstract: Ungulates often alter behavior and space use in response to interspecific competition. Despite observable changes in behavior caused by competitive interactions, research describing the effects of competition on survival or growth is lacking. We used spatial modeling to determine if habitat use by female mule deer ( Odocoileus hemionus ) was affected by other ungulate species prior to, during, and after parturition. We conducted our study in the Book Cliffs region of eastern Utah, USA, during 2019 and 2020. We used resource selection function (RSF) analysis to model space use of 4 ungulate species that potentially competed with mule deer: bison ( Bos bison ), cattle, elk ( Cervus canadensis ), and feral horses. We incorporated RSF models for competing species into a random forest analysis to determine if space use by mule deer was influenced by these other ungulate species. We used survival and growth data from neonate mule deer to directly assess potential negative effects of other ungulates. Habitat use by elk was an important variable in predicting use locations of mule deer during birthing and rearing. The relationship was positive, suggesting interference competition was not occurring. Survival of neonate mule deer increased as the probability of use by elk increased (hazard ratio = 0.185 ± 0.497 [SE]). Further, probability of use by elk in rearing habitat had no influence on growth of neonate mule deer from birth to 6 months of age, suggesting that exploitative competition was not occurring. Abstract : We analyzed potential competitive interactions between mule deer and other native and nonnative ungulates during the birthing and rearing period. We found no evidence of competitive interactions between mule deer and other ungulate species during birthing and rearing of young.